2015
DOI: 10.3109/03009742.2015.1055797
|View full text |Cite
|
Sign up to set email alerts
|

Atlas-based knee osteophyte assessment with ultrasonography and radiography: relationship to arthroscopic degeneration of articular cartilage

Abstract: (2016) Atlas-based knee osteophyte assessment with ultrasonography and radiography: relationship to arthroscopic degeneration of articular cartilage, Scandinavian Journal of Rheumatology, 45:2, 158-164,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 15 publications
3
50
2
Order By: Relevance
“…Cartilage damages identified by US were previously correlated with degenerative cartilage changes found by arthroscopy, but the lack of US findings does not exclude degenerative changes [30]. The association of the hyaline cartilage damageor loss with pain was demonstrated in US and MRI studies [2,13,[31][32][33]. In our study we found that cartilage damage was the most important predictor for knee pain, especially for pain evaluated by VAS.…”
Section: Inter-observer Agreementsupporting
confidence: 54%
See 1 more Smart Citation
“…Cartilage damages identified by US were previously correlated with degenerative cartilage changes found by arthroscopy, but the lack of US findings does not exclude degenerative changes [30]. The association of the hyaline cartilage damageor loss with pain was demonstrated in US and MRI studies [2,13,[31][32][33]. In our study we found that cartilage damage was the most important predictor for knee pain, especially for pain evaluated by VAS.…”
Section: Inter-observer Agreementsupporting
confidence: 54%
“…Of note, the authors did not take into consideration the presence of osteophytes at this level so their results could be biased. Podlipska et al [22], using the scale proposed by Koskiet al [32] for evaluating osteophytes and the distance from bone contour for meniscal protrusion, underlined the added value of US over radiography in knee OA management. One of the drawbacks of the study was that the authors did not correlate these findings with pain.…”
Section: Inter-observer Agreementmentioning
confidence: 99%
“…Multivariate linear regression analysis showed that medial inferior osteophytes were not a predictor for VAS score but were a predictor for WOMAC score. One of the limitations of our study is that we only described the presence or absence of osteophytes on the medial and lateral compartments and did not use a semiquantitative assessment as proposed by Koski et al…”
Section: Discussionmentioning
confidence: 99%
“…The definitions for osteophyte grades15 assessed from longitudinal images are as follows: Grade 0 – no osteophyte, Grade 1 – small osteophyte, Grade 2 – medium osteophyte, Grade 3 – large osteophyte. In these images, the same grade osteophytes are always present on both femoral (F) and tibial (T) margin.…”
Section: Figurementioning
confidence: 99%